Matrix effect on the degradation of fragrant aldehydes: oxidation versus chlorination in an antiperspirant formulation. (1st July 2013) - Ruyffelaere, Fanny; Marteau, Clémentine; Nardello‐Rataj, Véronique; Favier, Dominique; Vezin, Hervé; Aubry, Jean‐Marie
ABSTRACT: The oxidative degradation of several fragrant aldehydes in an antiperspirant base has been investigated. The different products formed have been detected and identified by GC‐MS. It is shown that, besides the oxidation products, i.e. mainly the corresponding acid resulting from the Baeyer–Villiger reaction, several unexpected chlorinated products are formed through interactions with aluminium chlorhydrate and the suspension agent. The supposed intermediate in the chlorination pathway is the acyl hypochlorite R(CO)OCl which can react according to either an ionic or a radical route. Reactive species involved in these mechanisms are Cl δ+ and Cl, respectively. The common intermediate for the autoxidation and oxychlorination processes is the peracid R(CO)OOH. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : The oxidative degradation of fragrant aldehydes such as Lilial in an antiperspirant base leads to the formation of autoxidation products, mainly the acid resulting from a Baeyer‐Villiger reaction, and to several chlorinated products formed through interactions with aluminum chlorhydrate and the suspension agent. The intermediate in the chlorination pathway is the acyl hypochlorite R(CO)OCl which can react according to an ionic or a radical route whereas the common intermediate for the autoxidation and oxychlorination processes is the peracid R(CO)OOH.